2016
DOI: 10.5539/gjhs.v8n12p248
|View full text |Cite
|
Sign up to set email alerts
|

Perception and Misperception of Health Enhancing Physical Activity among Urban Community Dwellers in Ibadan, Nigeria: Profiling the Underestimators, the Overestimators, and the Realists

Abstract: Background: The ability to initiate and sustain health enhancing behaviour including physical activity requires appropriate self-perception of such activities. This study was conducted to investigate whether a group of Nigerian urban community dwellers are able to demonstrate a good perception of their physical activity behaviour. Methodology:The study was a cross-sectional survey of 1,153 urban community dwellers from three local government areas of Ibadan, Southwest Nigeria. Physical activity perception was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Advantages - it takes into account small activities that are important for EE but that are usually neglected; 30 it was translated and validated for various countries; 30 33 34 this questionnaire has been found to be reliable for the measurement of physical activity in pregnant women with different intensities of obesity and can be used as a tool to detail physical activity. 35 …”
Section: Introductionmentioning
confidence: 99%
“…Advantages - it takes into account small activities that are important for EE but that are usually neglected; 30 it was translated and validated for various countries; 30 33 34 this questionnaire has been found to be reliable for the measurement of physical activity in pregnant women with different intensities of obesity and can be used as a tool to detail physical activity. 35 …”
Section: Introductionmentioning
confidence: 99%
“…This study has the potential to create points of intervention that will improve the management of hypertension and prevent dietary salt-related hypertension in future studies. Moreover, there is evidence that in the general population of Zambia, salt consumption exceeds that recommended by WHO [22]. This study is therefore, of clinical interest.…”
Section: Discussionmentioning
confidence: 87%
“…A Shanghai study (2022) found that only 2.8% of pregnant women achieved the level of prenatal PA recommended by the international guidelines ( 70). An adequate level of PA in Iran (2010) was found to be 39% (71), in Norway (2020) it was 14.6% (72), in India (2015) 18% (73), and in Nigeria (2014) 10.2% (74). These numbers prove the need to take systemic measures to promote PA during pregnancy in various countries, including underdeveloped countries.…”
Section: Discussionmentioning
confidence: 98%